On the effect of internal channels and surface roughness on the high-cycle fatigue performance of Ti-6Al-4V processed by SLM. (5th April 2018) - Günther, Johannes; Leuders, Stefan; Koppa, Peter; Tröster, Thomas; Henkel, Sebastian; Biermann, Horst; Niendorf, Thomas
Highlights: For SLM processed samples containing internal channels crack initiation is observed at channel surfaces and bulk porosity Despite distinct crack initiation sites fatigue life data are characterized by a low degree of scatter for a given geometry Fatigue lives of the different geometries tested are clearly affected by the ligament size A fracture mechanics based approach is able to capture differences in fatigue lives of the sample geometries considered Based on the findings presented the superior impact of crack growth life on the overall fatigue life is deduced Graphical abstract: Abstract: Selective laser melting (SLM) is an additive manufacturing process allowing for the production of metallic high performance materials and components with complex geometries. Therefore, possible applications are direct production of casting molds, tools or turbine blades with internal cooling channels for an optimized cooling efficiency. A disadvantage of the technology is the process-inherent surface roughness, which is critical especially under fatigue loading conditions. Since internal surfaces often cannot be smoothened due to limited accessibility, the objective of this study is to assess the fatigue properties of Ti-6Al-4V samples designed with internal axial channels featuring a rough as-built surface. Samples with various diameters and numbers of channels have been tested not always exhibiting a deterioration of the fatigue performance compared to solid samples. Subsequent fractography by scanning electron microscopy revealed distinct failure mechanisms. Besides the fatigue crack initiation on features of the unmodified internal surfaces, residual porosity in the bulk, i.e. lack-of-fusion defects, keyhole defects and gas pores, respectively, could be identified as crack origin. Relatively low scatter of fatigue lives found is attributed to rapid crack initiation and, thus, the dominant influence of the (micro-) crack growth regime.